2013
DOI: 10.14411/eje.2013.058
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differences in spectral sensitivity and wing colouration of 13 species of Japanese Thecline butterflies (Lepidoptera: Lycaenidae)

Abstract: Abstract. The correlation between dorsal wing colours and spectral sensitivity of the compound eyes of 13 species of thecline butterflies, consisting of 8 sexually monomorphic and 5 dimorphic species, was investigated. Spectral reflectance of the dorsal surfaces of the wings was measured using a spectrophotometer and spectral sensitivities using electroretinography. All 13 species examined showed a common basic pattern of spectral sensitivity with a primary peak at a wavelength of 440-460 nm. Detailed analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These are generated by nanoporous multi-layer photonic nanostructures which are located in the lumen of the cover scales (figures 8 and 9 ). The structural colours are important in the life of these insects, as they are used as sexual signalling colours [ 41 , 42 ], therefore their effective perceptibility is crucial. It seems likely that the changes in the wing scale nanoarchitectures have resulted from evolutionary pressure driven by perceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…These are generated by nanoporous multi-layer photonic nanostructures which are located in the lumen of the cover scales (figures 8 and 9 ). The structural colours are important in the life of these insects, as they are used as sexual signalling colours [ 41 , 42 ], therefore their effective perceptibility is crucial. It seems likely that the changes in the wing scale nanoarchitectures have resulted from evolutionary pressure driven by perceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Color sense in butterflies is widely known (Arikawa et al, 1987;Bernard and Remington, 1991;Qiu and Arikawa, 2003), including Theclini species (Imafuku and Tsuji, 2008;Imafuku, 2013). Further, it has been observed that males of the present species discriminated a brown wing model of the female from a green wing model of the male (Imafuku and Kitamura, 2015), and that males of the closely related Favonius taxila (Bremer) alit on a site with a bright green male model less frequently than on a site with a dull green male model (Imafuku and Hirose, 2016), suggesting that the bright wing color of males of this species has a negative effect on establishment of territories by conspecific males.…”
Section: Discussionmentioning
confidence: 99%